Throughput of wireless networks with Poisson distributed nodes using location information - Nardelli, Pedro H. J.; De Lima, Carlos H. M. [UNESP]; Alves, Hirley; Cardieri, Paulo; Latva-Aho, Matti (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This paper provides a statistical characterization of the individual achievable rates and the spatial throughput of bipolar Poisson wireless networks. We derive closed-form expressions for the probability density function of the achievable rates under two decoding rules: treating interference as noise, and jointly detecting the strongest interfering signals treating the others as noise. Based on these rules and the bipolar model, we approximate the expected maximum spatial throughput, showing the best performance of the latter decoding rule. We show that, when the same decoding rule and density are considered, the cognitive spatial throughput always outperforms the other option.